Development of EST-derived SSR markers using next-generation sequencing to reveal the genetic diversity of 50 chrysanthemum cultivars. (June 2015) - Jo, Kyoung-Min; Jo, Yeonhwa; Chu, Hyosub; Lian, Sen; Cho, Won Kyong
Abstract: Chrysanthemum plants are popular worldwide as cut flowers, potted, and in gardens. Several hundred cultivars have been commercialized, indicating that there is substantial genetic variations that can be manipulated under cultivations to produce a wide array of phenotypic variation. To study the genetic diversity of chrysanthemum cultivars in Korea, we first identified simple sequence repeats from chrysanthemum expressed sequence tags generated by FLX 454 sequencing. A total of 1109 ESTs out of 18, 226 chrysanthemum ESTs were identified to carry SSRs. A total of 16 out of 46 primer pairs exhibited several polymorphisms among 50 chrysanthemum cultivars. The number of alleles per locus varied from 1 to 15, with an average of 6.25 alleles. The expected heterozygosity ranged from 0 to 0.8958, whereas polymorphism information content ranged from 0 to 0.8872. Based on polymorphisms using 16 SSR markers, a phylogenetic tree was generated revealing four groups within the 50 cultivars showing various levels of genetic diversity. The 16 polymorphic chrysanthemum SSR markers generated in this study would be useful for studies of the genetic conservation, diversity, and population structure of commercial chrysanthemum cultivars as well as closely related species. Highlights: We identified simple sequence repeats from 18, 226 chrysanthemum ESTs. We identified 16 primer pairs out of 46 primer pairs exhibited several polymorphisms. Genetic diversity of 50 chrysanthemum cultivars in Korea was examined by 16 polymorphic SSR markers. Phylogenetic analysis identified four major groups within the 50 cultivars showing various levels of genetic diversity.